Construction Safety Practice on Pre-stressed Bridge Construction: A Case Study of Parasi District - Subedi, Krishna Keshab; Basnyat, Dilman Singh (International Journal on Engineering Technology and Infrastructure Development, 2024)
Prestressed bridge construction is latest technique of bridge construction in Nepal comparison to other techniques. Since these techniques use more mechanical tools and equipment than others; hazards are more. This research assessed the safety in prestressed bridge construction involving stakeholder's perception. The study area is Parasi district of Lumbini province. Seven prestressed bridge sites were selected for the study which included constructed and also the under-construction sites. Primary data was collected by Key informant interview (KII) Survey and field visit whereas secondary data was collected from respective office of client, contractor's office, and Department of Roads (DOR). Multi-stakeholders were identified and KII survey was done for stakeholders with the use of questionnaire prepared. This resulted in account of stakeholders' perception towards availability and supporting of various control measures in site. The research also aimed to analyze the occupational hazards (OHs) with their causes and characterized them considering each of the internal and external factors and assess the preventive and control measures of occupational hazards.